Isolation and characterization of antibody fragments selective for specific protein morphologies from nanogram antigen samples. (7th March 2013) - Kasturirangan, Srinath; Reasoner, Tim; Schulz, Philip; Boddapati, Shanta; Emadi, Sharareh; Valla, Jon; Sierks, Michael R.
<x xml:space="preserve">Abstract</x> We developed atomic force microscope (AFM)‐based protocols that enable isolation and characterization of antibody‐based reagents that selectively bind target protein variants using low nanogram amounts or less of unpurified starting material. We isolated single‐chain antibody fragments (scFvs) that specifically recognize an oligomeric beta‐amyloid (Aβ) species correlated with Alzheimer's disease (AD) using only a few nanograms of an enriched but not purified sample obtained from human AD brain tissue. We used several subtractive panning steps to remove all phage binding nondesired antigens and then used a single positive panning step using minimal antigen. We also used AFM to characterize the specificity of the isolated clones, again using minimal material, selecting the C6 scFv based on expression levels. We show that C6 selectively binds cell and brain‐derived oligomeric Aβ. The protocols described are readily adapted to isolating antibody‐based reagents against other antigenic targets with limited availability. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29: 463–471, 2013